Religion-State Interaction at the Local Level: Key Findings from a Survey of Religion and Local Elected Officials - Adler, Gary J., Jr. (Journal for the scientific study of religion, 2022)
Relationships between religion and state are a core focus for social scientists, but little is known about a central set of actors in “church-state” relations in the United States: local elected officials (mayors, town councilpersons, city commissioners). We report on a unique, representative survey of local elected officials, examining their religiosity, their interactions with religion through governance (prayers, meetings, symbol placement requests), and their preferences for religion-state relations. Our results show that local elected officials are no more religious than the general adult public, that they interact with religion in their formal governance at low rates, and that a quarter strongly prefer increased state engagement with religion. Minority religious affiliation, Democratic political affiliation, and urban context predict opposition to religion-state engagement. We describe how local elected officials may produce local regimes of religion-state interaction that vary by geographic location and suggest pathways for future research.